Rancang Bangun Sistem Manajemen Proyek Perangkat Lunak Berbasis Web Menggunakan Metode Rational Unified Process - Agustin, Yoga Handoko; Kustiana, Ruli M (Institut Teknologi Garut, 2025)
The success of companies in the technology sector greatly depends on effective project management. At PT. Artivisi Intermedia Jakarta, the software project management process faces several challenges, including schedule delays, inadequate team coordination, and difficulties in tracking project progress due to the use of semi-manual systems based on Microsoft Excel. This research focuses on the design and implementation of a web-based project management system to address these issues, with an emphasis on optimizing time management and human resources. The development framework adopted is the Rational Unified Process (RUP), chosen for its iterative and structured approach, which covers four main phases: inception, elaboration, construction, and transition. Unified Modeling Language (UML) was employed for system modeling, while system functionality was tested using the Black Box Testing method, and usability was measured using the System Usability Scale (SUS). The results show that the system was successfully developed in its entirety, with Black Box testing confirming that all core functions were “Valid.” Furthermore, usability testing involving 20 respondents yielded a SUS score of 72.8, indicating that the system is classified as “Good” and “Acceptable” to users. Therefore, the developed system provides a functional solution to improve efficiency and transparency in project management at PT. Artivisi Intermedia Jakarta. The contribution of this study lies in presenting a validated systemic solution for technology companies facing similar challenges, with practical implications for optimizing project execution.